Kinetics of Phenotypic and Functional Changes in Mouse Models of Sponge Implants: Rational Selection to Optimize Protocols for Specific Biomolecules Screening Purposes - Lanna, Mariana Ferreira; Resende, Lucilene Aparecida; Aguiar-Soares, Rodrigo Dian de Oliveira; de Miranda, Marina Barcelos; de Mendonça, Ludmila Zanandreis; Melo Júnior, Otoni Alves de Oliveira; Mariano, Reysla Maria da Silveira; Leite, Jaqueline Costa; Silveira, Patricia; Corrêa-Oliveira, Rodrigo; Dutra, Walderez Ornelas; Reis, Alexandre Barbosa; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
The characterization of immune events in sponge implants would be useful to identify the immunological events that could support the selection of optimized protocols for novel applications of this model. Here, the changes in histological/morphometric, immunophenotypic and functional features of infiltrating leukocytes were assessed in sponge implants for Swiss, BALB/c, and C57BL/6 mice. A gradual increase of fibrovascular stroma and a progressive decrease in leukocyte infiltration, mainly composed of polymorphonuclear cells with progressive shift towards mononuclear cells at late time-points, were observed over time. Usually, Swiss mice presented more prominent immune response with late mixed pattern of cytokine production. While BALB/c mice showed an early activation of the innate response with a controlled cytokine profile, C57BL/6 mice presented a typical early pro-inflammatory response with persistent neutrophilic involvement. A rational selection of the ideal time-point/mouse-lineage would avoid bias or tendentious results. Criteria such as: low number of increased biomarkers, no recruitment of cytotoxic response, minor cytokine production and lower biomarker connectivity guided the choice of the best time-point for each model (Day5/Swiss; Day7/BALB/c; Day6/C57BL/6) with wide application for screening purposes, such as identification of therapeutic biomolecules, selection of antigens/adjuvants, and follow-up of innate and adaptive immune response to vaccines candidates.